Gastric lap-band infection due to Mycobacterium abscessus presenting as new-onset ascites in a cirrhotic patient. Issue 8 (2nd August 2016) - Kahn, Allon; Agrwal, Neera; Carey, Elizabeth J.; Madura, James A.; Hewitt, Winston R.; Lambert, Karen L.; Grys, Thomas E.; Vikram, Holenarasipur R.
Abstract: Nontuberculous mycobacteria are ubiquitous environmental organisms that are infrequently implicated as pathogens. Peritoneal infection with nontuberculous mycobacteria is rare and published reports are most commonly associated with peritoneal dialysis. This study describes a case of a 41-year-old woman with cirrhosis who had Mycobacterium abscessus peritonitis and an abdominal abscess resulting from infection of a remotely placed gastric band (Lap-Band; Apollo Endosurgery, Inc).